Beetroot juice intake with different amounts of nitrate does not change aerobic exercise-mediated responses in heart rate variability in hypertensive postmenopausal women: A randomized, crossover and double-blind study - Victor Hugo V. Carrijo; Ana Luiza Amaral; Igor M. Mariano; Tállita Cristina F. de Souza; Jaqueline P. Batista; Erick P. de Oliveira; Guilherme M. Puga (Elsevier, 2021)
Background/Objective: To compare the acute effects of a single dose of beetroot juice (BJ) with different concentrations of nitrate (NO3−) on heart rate variability (HRV) in postmenopausal hypertensive women. Methods: Thirteen hypertensive postmenopausal women (58.1 ± 4.6 years of age and 27 ± 4 kg/m2 of BMI) completed the protocol that consisted of three visits with different beverage intakes in a randomized and crossover design. The three beverages were BJ with a high content of nitrate (high-NO3-), BJ with a low content of nitrate (low-NO3-), and an orange flavored non-caloric drink (OFD). Heart rate (HR) were evaluated during 20 min after sitting rest at 7:20 a.m. (baseline), after they drank one of the drinks, and remained at sitting rest for 120 min and then performed 40 min of aerobic exercise at 65-70% of the HR reserve on a treadmill. HR was recorded for 90 min after exercise for time, frequency, and non-linear domains of HRV index analysis. Results: Two-way ANOVA showed that there were no interaction effects (time∗sessions) in any of the HRV indexes after exercise in all three sessions. HRV indexes increased after exercise (p = <0.05) similarly in all three sessions when compared with the baseline time point. Conclusion: Therefore, a single dose of BJ, independent of NO3− content, does not change aerobic exercise-mediated responses in HRV indexes in hypertensive postmenopausal women.